(untitled) (Research in Agriculture Livestock and Fisheries, 2019)
An experiment was conducted at the Soil Science Field Laboratory of Bangladesh Agricultural University, Mymensingh during Aman season of 2016 to evaluate the effects of deep placement of N fertilizers in the form of urea super granule (USG) and NPK briquettes in comparison with prilled urea (PU) on nitrogen use efficiency and yield of BRRI dhan49. The soil was silt loam in texture having pH 6.27, organic matter content 1.95% and total N 0.136%. The experiment was laid out in a Randomized Complete Block Design (RCBD) with eight treatments and three replications. The treatments include T1 (Control), T2 (PU, 104 kg N ha-1), T3 (USG, 104 kg N ha- 1), T4 (USG 78 kg N ha-1), T5 (USG, 52 kg N ha-1), T6 (NPK briquettes, 104 kg N ha-1), T7 (NPK briquettes, 78 kg N ha-1) and T8 (NPK briquettes, 52 kg N ha-1). All the treatments except T6, T7 and T8 received 16 kg P and 42 kg K ha-1 from TSP and MoP, respectively. In T6, T7 and T8 treatments, P and K were supplied from NPK briquettes. The PU was applied in three equal splits. The USG and NPK briquettes were deep placed 10 DAT and the briquettes were placed at 8-10 cm depth between four hills at alternate rows. Application of PU, USG and NPK briquette under alternate wetting and drying (AWD) condition exerted significant influence on yield attributes as well as grain and straw yields of BRRI dhan49. The maximum grain yield of 6311 kg ha-1 (100% increases over control) and straw yield of 6956 kg ha-1 was recorded in T3 (USG, 104 kg N ha-1). The second highest grain yield of 5865 kg ha-1 produced by T2 (PU, 104 kg N ha-1) was statistically similar with T4 (USG 78 kg N ha-1) and T6 (NPK briquettes, 104 kg N ha-1). The lowest grain yield (3155 kg ha-1) and straw yield (3908 kg ha-1) were recorded in T1 (Control). The deep placement of USG and NPK briquettes enhanced both the recovery of applied N and N use efficiency in comparison with broadcast application of prilled urea. The T5 (USG, 52 kg N ha-1) showed maximum apparent N recovery, and N use efficiency. Next to T5, the T4 depicted the position in respect of N recovery and N use efficiency. So the application of 78 kg N ha-1 in the form of USG can be recommended for the production of BRRI dhan49. Res. Agric., Livest. Fish.6(1): 27-33, April 2019